Chemical Abundances in the Milky Way’S Nuclear Stellar Disc - Rojas-Arriagada, A (EDP Sciences, 2025)
Context. The nuclear stellar disc (NSD) is a rotating, disc-like structure in the Galactic centre; it is believed to have a distinct star formation history and a predominantly old stellar population. However, its formation history and evolutionary links to other structures in the Galactic centre remain uncertain. Studying the chemical evolution of the NSD could provide new insights into this region and key epochs in the Milky Way’s evolution, yet such studies remain rare. Aims. We created the first comprehensive chemical census of the NSD by deriving abundance trends for 18 elements in nine M giants in the metallicity range −1.0 <[Fe/H]< +0.5. By comparing these trends with those of other Galactic populations – including the nuclear star cluster (NSC), the inner bulge, and the thin and thick discs – we seek to understand the chemical relationships between these structures. Methods. To mitigate the extreme optical extinction along the line of sight, we obtained high-resolution H- and Ks-band spectra of NSD stars using the IGRINS spectrometer mounted on the Gemini South telescope. The observed M giants and stars from comparison populations were analysed in an consistent manner to minimise systematic uncertainties. Results. The abundance trends of NSD stars exhibit strong similarities with those of the inner-bulge and NSC populations across a broad range of elements with different chemical evolution histories. The trends for α elements, Al, Cr, Mn, Co, Ni, Cu, Zn, and neutron-capture elements align closely with the local thick-disc behaviour at sub-solar metallicities. At super-solar metallicities, most elements follow the NSC and inner-bulge trends. Sodium is the only element exhibiting a distinct trend, with enhanced abundances in the NSD and NSC compared to both thin-disc and inner-bulge stars. Conclusions. The chemical similarity of most of the 18 elements investigated, including Na, suggests that the NSD likely shares an evolutionary history with the NSC, and possibly with the inner-disc sequence. Further studies are required to determine potential evolutionary links to the complex stellar system Liller 1 and metal-rich globular clusters. We find no evidence of typical globular cluster abundance signatures in our NSD stars with sub-solar metallicities. Our study demonstrates the feasibility of obtaining high-quality abundance data even in highly dust-obscured regions of the Milky Way, paving the way for future surveys. © The Authors 2025.